Dampak Pajanan Timbal terhadap Anemia Pekerja dan Strategi Intervensi - Lasiyo, Yumna Satyani; Ramdan, Doni Hikmat (Fakultas Kesehatan Masyarakat Universitas Andalas, 2024)
Lead poisoning is still a major case of industrial and environmental problems in developing countries. In the last decade, several studies have been conducted on the impact of lead exposure on health, one of which is the risk of anemia in both workers and communities around exposed factories. The aim of this research is to determine the impact of lead on the risk of anemia in the work environment, and intervention strategies that can be carried out by the parties involved. This research includes a literature review obtained from a search using the PRISMA 2009 system. Of the 246 journals obtained from the first search, 20 journals were included in this research. The research results showed that factors that influence blood lead levels are environmental conditions, work area, use of PPE, worker hygiene behavior, and duration of work, either daily or long term. Anemia is one of the dominant symptoms and has an impact on work productivity. Intervention strategies for cases of anemia due to lead exposure can be carried out using the principle of hierarchy control and improving individual hygiene behavior, as well as providing additional supplements. In severe cases, chelation and alternative therapies need to be considered. Controlling the impact of lead exposure needs to be carried out by company management and requires worker participation to be protected from the effects of intoxication on health.